Exploring the response of yellow lupine (Lupinus luteus L.) root to drought mediated by pathways related to phytohormones, lipid, and redox homeostasis - Sebastian Burchardt; Małgorzata Czernicka; Agata Kućko; Wojciech Pokora; Małgorzata Kapusta; Krzysztof Domagalski; Katarzyna Jasieniecka-Gazarkiewicz; Jacek Karwaszewski; Emilia Wilmowicz (BMC Plant Biology)
Abstract Background Yellow lupine (Lupinus luteus L.) is a high-protein crop of considerable economic and ecological significance. It has the ability to fix atmospheric nitrogen in symbiosis with Rhizobium, enriching marginal soils with this essential nutrient and reducing the need for artificial fertilizers. Additionally, lupine produces seeds with a high protein content, making it valuable for animal feed production. However, drought negatively affects lupine development, its mutualistic relationship with bacteria, and overall yield. To understand how lupine responds to this stress, global transcriptome sequencing was conducted, along with in-depth biochemical, chromatography, and microscopy analyses of roots subjected to drought. The results presented here contribute to strategies aimed at mitigating the effects of water deficit on lupine growth and development. Results Based on RNA-seq, drought-specific genes were identified and annotated to biological pathways involved in phytohormone biosynthesis/signaling, lipid metabolism, and redox homeostasis. Our findings indicate that drought-induced disruption of redox balance characterized by the upregulation of reactive oxygen species (ROS) scavenging enzymes, coincided with the accumulation of lipid-metabolizing enzymes, such as phospholipase D (PLD) and lipoxygenase (LOX). This disruption also led to modifications in lipid homeostasis, including increased levels of triacylglycerols (TAG) and free fatty acids (FFA), along with a decrease in polar lipid content. Additionally, the stress response involved alterations in the transcriptional regulation of the linolenic acid metabolism network, resulting in changes in the composition of fatty acids containing 18 carbons. Conclusion The first comprehensive global transcriptomic profiles of lupine roots, combined with the identification of key stress-responsive molecules, represent a significant advancement in understanding lupine’s responses to abiotic stress. The increased expression of the Δ12DESATURASE gene and enhanced PLD activity lead to higher level of linoleic acid (18:2), which is subsequently oxidized by LOX, resulting in membrane damage and malondialdehyde (MDA) accumulation. Oxidative stress elevates the activities of superoxide dismutase (SOD), ascorbate peroxidase (APX), and catalase (CAT), while the conversion of FFAs into TAGs provides protection against ROS. This research offers valuable molecular and biochemical candidates with significant potential to enhance drought tolerance . It enables innovative strategies in lupine breeding and crop improvement to address critical agricultural challenges.